Clinical and Neurological Manifestations and an Integrated Approach to Stroke Rehabilitation - Sharipov F. R. (Scholars Digest Publishing, 2023)
Despite the fact that primary prevention plays a decisive role in reducing mortality and disability due to stroke, a significant effect in this regard is the optimization of the system of care for patients with cerebrovascular diseases, the introduction of therapeutic and diagnostic standards for these patients, including rehabilitation measures and prevention of recurrent strokes. The development and implementation of common principles for the management of patients with cerebrovascular diseases should help optimize the diagnostic approach and choice of therapeutic measures to ensure the best outcome of the disease.
Keywords: ischemic stroke, Scandinavian scale, neurological symptoms, computed tomography.